How do consumers evaluate buffalo meat? - Ricardo Alexandre Silva Pessoa; Marilia Celeste Tavares Fernandes; María Luciana Menezes Wanderley Neves; Thales Freire Arival; Fabiana Carvalho Vasconcelos Pessoa (Revista Científica)
Consumers have been the target of studies since they constitute the focal point of production chains. The objective of this study was to analyze the opinions of a given population and the consumers’ perception regarding industrialized and commercialized buffalo meat in the metropolitan region of Recife, in the state of Pernambuco, located in the Northeast region of Brazil. A questionnaire was applied in August and September 2022, and the technique used for the research was the survey. The research filter was the affirmative answer to the question about the purchase and consumption of buffalo meat products. The test was applied electronically, structured in closed, open, and dichotomous questions, to obtain qualitative and quantitative data from 178 consumers of buffalo meat. The questionnaire addressed the following aspects: age, sex, family income, the most consumed meat cut, the main aspects observed in fresh and ready-to-eat buffalo meat and the determinants in the choice, degree of satisfaction with the product, prior knowledge of buffalo meat and the degree of satisfaction with the consumption of hamburgers and sausages. Data were tabulated and subjected to descriptive statistical analysis using the Excel 2013 Office version program. The proportion of male and female consumers was 48.0% and 52.0%, respectively. The average age observed was 37 years. The evaluated consumers have an average family income of more than US$ 550,00. The most consumed meat cuts are those considered “day-to-day”, emphasizing the topside, knuckle, eye round, flat, minced meat, and sun-dried meat, making up 67.8% of the choices. Consumers reported choosing meat primarily considering cost accessibility, product quality, and sensory characteristics, high-lighting flavor and tenderness. The degree of satisfaction was between satisfied and very satisfied for 92.0% of the assessed consumers. 81.0% of consumers said they had never consumed buffalo meat or meat products. The buffalo meat burger was rated good by 35.0% of consumers and very good by 62.0%. It is observed that the commercial availability of buffalo meat is a determining factor for consumption since the degree of rejection of buffalo meat products is minimal.